The Influence of Brand Trust, Brand Image, and E-WOM on Repurchase Intention : A Study on Consumers of the International Pizza Hut Franchise in Denpasar City - I Gst. Agung Gede Dirgantara Kusumajaya; I Gst. A. Kt. Gd. Suasana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Repurchase intention represents a tangible form of consumer satisfaction toward a product or service offered by a brand, which fosters a desire among consumers to make repeat purchases of the same brand. Several factors influence repurchase intention, including brand trust, brand image, and electronic word of mouth (e-WOM). The existence of repurchase intention has significant implications for various industries, particularly the food and beverage (F&B) sector. One of the most recognized F&B franchises in Indonesia is the international brand Pizza Hut. This study aims to analyze the influence of brand trust, brand image, and e-WOM on repurchase intention among consumers of the international Pizza Hut franchise in Denpasar City. The research was conducted on consumers of the international Pizza Hut franchise in Denpasar, with a total of 100 respondents selected using purposive sampling. Data were collected through the distribution of offline questionnaires. The data analysis techniques employed in this study include multiple linear regression, as well as descriptive and inferential analyses using SPSS software. The findings indicate that brand trust, brand image, and e-WOM have a positive and significant effect on repurchase intention. Based on these findings, it is recommended that the international Pizza Hut franchise consider the aspects of brand trust, brand image, and e-WOM as key strategies to enhance consumers’ repurchase intention.